2018
DOI: 10.1177/0963689718820271
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Neural Progenitor Cells (NPC) into Putamina of Parkinsonian Patients: A Case Series Study, Safety and Efficacy Four Years after Surgery

Abstract: Individuals with Parkinson’s disease (PD) suffer from motor and mental disturbances due to degeneration of dopaminergic and non-dopaminergic neuronal systems. Although they provide temporary symptom relief, current treatments fail to control motor and non-motor alterations or to arrest disease progression. Aiming to explore safety and possible motor and neuropsychological benefits of a novel strategy to improve the PD condition, a case series study was designed for brain grafting of human neural progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 73 publications
0
49
0
Order By: Relevance
“…One year after cell grafting, all but one of the seven patients completing the study showed various degrees of motor improvement, and five of them showed better response to medications. Moreover, none of the patients showed unwanted motor disturbances, tumor formation, or any immune responses to the grafted cells, demonstrating the safety and efficacy of this transplantation [36].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…One year after cell grafting, all but one of the seven patients completing the study showed various degrees of motor improvement, and five of them showed better response to medications. Moreover, none of the patients showed unwanted motor disturbances, tumor formation, or any immune responses to the grafted cells, demonstrating the safety and efficacy of this transplantation [36].…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, the intravenous administration of NPCs in a preclinical animal model of traumatic SCI improved hind limb functional recovery, axons regenerations, and differentiation into cholinergic neuron cells [31,[33][34][35]. The safety and efficacy of NPCs as cell therapy was investigated not only in preclinical animal models but also in human patients [36]. In this context, Madrazo et al transplanted into the putamina of Parkinsonian patients human NPCs obtained from first trimester human fetal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently completed Phase 1 trial, Celevie’s NPCs were implanted into the putamen of seven patients with mild-to-moderate Parkinson’s disease (PD). At the 4-yr follow-up study, six of the seven patients showed significant improvements in Unified Parkinson’s Disease Rating Scale part III (measuring motor function) compared to their previous baseline scores 21 . While a definitive conclusion on NPC efficacy will require larger controlled PD trials, these initial results suggest that transplanted NPCs have a positive and lasting effect on neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 83%
“…Human NPCs were obtained according to NIH Ethical Guidelines and have been fully described in previous studies 21 23 . Briefly, NPCs were grown for 13 doublings in ultra-low attachment culture flasks under feeder-free conditions in serum and xeno-free Eagle’s essential medium (Hyclone, Logan, UT, USA), supplemented with Gem21 (Gemini Bio-Products, Sacramento, CA, USA), epidermal growth factor (Peprotech, Rocky Hill, NJ, USA), basic fibroblast growth factor (Peprotech), transforming growth factor alpha (Peprotech), insulin-like growth factor I (Peprotech), leukemia inhibitory factor (Millipore, Temecula, CA, USA), calcium chloride (Fisher Scientific, Waltham MA, USA), Glutamax (Invitrogen, Carlsbad, CA, USA), non-essential amino acids (Hyclone), and an N2 supplement (Invitrogen), all of which were added at proprietary concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, results from the 4-years follow-up of the HSCfPD trial (NCT02780895, 2016) from Celavie Biosciences described an alternative method for monitoring immune responses. In this trial that used a cell-based product consisting of undifferentiated NPCs derived from human fetal brain tissue, named OK99, researchers showed a lack of an elicited immune response in one month CyA-immunosuppressed patient's blood samples analyzed by flow cytometry for both NPC-specific antibodies and antibody-dependent cell-mediated cytotoxicity, and after CyA treatment withdrawal at six months after grafting (Madrazo et al, 2019).…”
Section: Neuroinflammation Markers: Assessment In Cell-based Clinicalmentioning
confidence: 99%